Ash behavior of various fuels: The role of the intrinsic distribution of ash species. (1st October 2019) - Reinmöller, Markus; Schreiner, Marcus; Guhl, Stefan; Neuroth, Manuela; Meyer, Bernd
Highlights: A broad variety of seven different fuels are ashed at 200, 450, and 815 °C. Distribution of the ash species depends on type of fuel and it specific origin. Fuel and particle properties determine the residual carbon in low temperature ash. The distribution of the ash species affects alkali release and ash fusion behavior. Abstract: In the present study, seven different fuels – comprising three coals (hard coal, two brown coals), two contaminated biomasses/anthropogenic wastes (refuse-derived fuel/RDF, sewage sludge), and two biomasses (oat husks, bamboo) – are investigated. A complete fuel analysis as well as a determination of the particle size distributions of all ground feedstocks are performed prior to ashing. Ashes of these fuels are generated with the aid of different ashing methods and related temperatures, i.e. a plasma-assisted low temperature ash (LTA) at around 200 °C, a medium temperature ash (MTA) at 450 °C, and a high temperature ash (HTA) at 815 °C. By SEM/EDX analysis, distinct differences in the distribution of ash species based on selected main elements in LTA ash of all fuels are detected. The ash particles generated by the LTA method illustrate both origin and distribution of ash species in the particles close to the initial state due to a comparably low temperature. For this method, the achieved carbon conversion can be directly related to specific fuel and particle properties. A selective release of alkali oxides (K2 O, Na2 O) into the gas phase due to vaporization is monitored as a function of ashing temperature. Thus, the presence or absence of a gas phase transfer of the alkali oxides is concluded based on the formation of mineral phases incorporating those species and the requirement of a homogeneous distribution of the alkali capturers. Finally, distinct changes are observed in the ash fusion behavior of the different fuels based on different ashing temperatures, element distribution, and the applied atmosphere, which have represented different thermochemical conversion techniques.